Annual Plan 1980-81 Planning Commission (State Plan Division) - Planning Commission (Planning Commission, 1980)
It may be noted that the pre-actual level of expenditure at Rs 475.52 crores is higher than the level reported earlier by about Rs 9 crores. In other words the shortfall in expenditure on the basis of the pre-actuals now reported by the State Government will work out to about Rs 16 crores as against Rs 25 crores estimated earlier
Planning Commission
Planning Commission